Young Children's Spontaneous Manifestation of Self-Regulation and Metacognition during Constructional Play Tasks. Issue 13 (April 2017) - Spektor-Levy, Ornit; Basilio, Marisol; Zachariou, Antonia; Whitebread, David
The value of self-regulation for academic achievement is well established. Thus it is paramount to understand how these abilities are developed throughout childhood and to develop research methodologies appropriate to the abilities of young children. In light of this need, we analyzed performances of primary school children in two constructional play tasks: The Train Track Task (TTT) and the LEGO® Building Task (LBT). We asked: To what extent do young children manifest spontaneous self-regulatory abilities during constructional play tasks? To what extent is the manifestation of these abilities task dependent? The sample consisted of 106 children in Year 1 to 5 in the United Kingdom (i.e., aged 5 to 10 years). All participants were given the same tasks and were video-recorded. Clips were coded following the MetaSCoPE coding scheme. Results show that the different components of self-regulation do develop between Years 1 and 5 but not at a constant pace. Findings reveal inconsistency regarding the question of whether self-regulation abilities are task dependent. Our findings hold practical implications: Constructional play tasks are good opportunities to reveal young children's self-regulation abilities in class. The development of teachers' awareness may help to better understand children's cognitive, affective, and social development and to adjust learning activities to the needs of young individuals.